Identifikasi dan Pengendalian Jamur Busuk Putih Buah Salak dengan Ekstrak Bunga Kecombrang (Nicolaia speciosa) - Aries Pratomo; Christanti Sumardiyono; Y. M.S. Maryudani (Jurnal Perlindungan Tanaman Indonesia, 2009)
One of the important disease on snakefruit (Salacca edulis) is fruit rot disease with white symptom. Control of snake fruit diseases is better when natural compounds rather than chemicals pesticide were used which might cause consumer hazard. Several of plant extract i.e. from Zingiberaceae which have antimicrobial activity had been studied. The purpose of this study were to identify the pathogen of white rot and to know the effect of torch ginger’s flower (Nicolaia speciosa) extract on disease development. The spores was identified under microscopic condition from diseased fruits and isolates. Torch ginger’s flowers was extracted in ethanol. After removal of the ethanol the crude extract was dissolved with distilled water. Food Poisoned Technique was done to evaluate its influence in vitro. Both detached and clustered fruits were sprayed with the extract then inoculated with the pathogen. The result showed that the pathogen was Chalaropsis sp. Detached snakefruit was more susceptible to Chalaropsis sp. infection than those in cluster. In vitro test showed 48–50 % of torch ginger’s flower extract in water inhibit 90% of colony growth. The extract inhibited the development of Chalaropsis sp. in detached snakefruit or in cluster ones. Concentrated extract protected snakefruit up to 100% from Chalaropsis sp. infection.